2020
DOI: 10.3390/su12176863
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Behaviour of Olive Oil Tourists: A Cluster Analysis in Southern Spain

Abstract: Olive oil tourism is a recent development in the countries of the Mediterranean basin, but it is now spreading to other regions of the world. The main reasons people are choosing this special interest tourism (SIT) are to find out about the culture surrounding olive oil and to enjoy the whole host of activities related to the product. This has led to the creation of strong links between olive oil tourism and other types of special interest tourism. The studies undertaken thus far to characterise the profile of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 30 publications
2
10
0
1
Order By: Relevance
“…This result is in line with the results of Pulido-Fernández et al (2021) and Pourfakhimi et al (2021). From a general perspective, Pulido-Fernández et al (2021) found that tourists consider olive oil-based activities as beneficial to health. More specifically, Pourfakhimi et al (2021) found empirical support for the causal relationship linking involvement with food experiences and improvements in personal wellbeing.…”
Section: Discussion Of Resultssupporting
confidence: 89%
“…This result is in line with the results of Pulido-Fernández et al (2021) and Pourfakhimi et al (2021). From a general perspective, Pulido-Fernández et al (2021) found that tourists consider olive oil-based activities as beneficial to health. More specifically, Pourfakhimi et al (2021) found empirical support for the causal relationship linking involvement with food experiences and improvements in personal wellbeing.…”
Section: Discussion Of Resultssupporting
confidence: 89%
“…The hotel industry under the change of institutional logic is also affected [7], directly affecting the quality of the tourism. There has been some research into tourists' emotional experiences, including how tourists may be attracted through appeal to emotions and the services provided at destinations [8][9][10][11], place attachment, and residents' attitudes and intentions toward tourism behavior [12]. How to effectively regulate holiday tourism to promote sustainable development and prevent significant negative impacts is a crucial issue that warrants the attention of national and local governments.…”
Section: Introductionmentioning
confidence: 99%
“…The production of this type of residue has increased considerably in recent decades, mainly in the countries of the Mediterranean basin, where olive oil production has traditionally been concentrated ( Gómez et al, 2010 ). Spain produces nearly 50% of the total volume of olive oil, making it the world’s leading producer ( Ministerio de Agricultura, Pesca y Alimentación, 2021a ; Pulido-Fernández et al, 2020 ). Industrialization and the development of advanced technology for oil extraction have led to increased production of AWBs in this sector ( Gómez et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%